Analysis and Evaluation of Productivity Using the Marvin E. Mundel Method and the Productivity Evaluation Tree (PET) at PT. YZ - Endang Palupi Sumarto; Elfitria Wiratmani; Fatoni Fatoni (Jurnal Teknologi dan Manajemen, 2024)
PT. YZ is currently still not optimal in utilizing the resources it has (input) so that the results (output) produced are not in accordance with the target which results in a decrease in company productivity and so productivity measurements must be carried out in the company. Besides that, at PT. YZ has never conducted a thorough productivity measurement during the production process. Therefore, in this study, productivity measurements were carried out with the aim of knowing the results of measuring productivity levels at PT. YZ, to find out the factors causing a decrease in productivity levels and evaluate productivity against measurement results that have low productivity. The proper method for analyzing these problems is to use the Marvin E Mundel method to measure productivity and the Productivity Evaluation Tree (PET) method is used to evaluate productivity issues. In carrying out processing using this method, it is assisted by the Embarcadero-Dev C ++ Software. Based on the results of research using the Marvin E. Mundel method, it was found that company productivity had decreased, namely that in 2021 total productivity was 1.14 and in 2022 total productivity was 1.13. The cause of the decline in company productivity is that the labor factor is not clearly regulated for sanctions and rewards for the company; the raw material factor is the long distance of delivery from the raw material supplier to the production site; and the energy factor has not yet carried out accurate calculations regarding the use of electricity for the process. Production and machine factors have not yet established a machine maintenance schedule. The evaluation results using the Productivity Evaluation Tree (PET) method show that total productivity has increased; in 2022, total productivity was 1.13, and in 2023, total productivity was 1.15. To increase productivity, this was done by reducing input, namely the number of workers. By reducing the number of workers, productivity increases.